2019
DOI: 10.1007/s00234-019-02265-2
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of dynamic contrast-enhanced magnetic resonance imaging data in primary brain tumours: a comparison of Tofts and shutter speed models

Abstract: PurposeThe purpose of this study is to investigate the robustness of pharmacokinetic modelling of DCE-MRI brain tumour data and to ascertain reliable perfusion parameters through a model selection process and a stability test.MethodsDCE-MRI data of 14 patients with primary brain tumours were analysed using the Tofts model (TM), the extended Tofts model (ETM), the shutter speed model (SSM) and the extended shutter speed model (ESSM). A no-effect model (NEM) was implemented to assess overfitting of data by the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…In comparison, these two transports are modeled using one parameter, transfer constant ( K trans ), in the Tofts or extended Tofts model. Interested readers could refer to [ 31 , 32 ] for a review on the topic.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, these two transports are modeled using one parameter, transfer constant ( K trans ), in the Tofts or extended Tofts model. Interested readers could refer to [ 31 , 32 ] for a review on the topic.…”
Section: Introductionmentioning
confidence: 99%
“…A non-linear least-square fitting ‘lsqcurvefit’ routine in MATLAB was used in all models. For model fitting, the initial parameter values were based on the literature values [ 38 , 39 ]. A hybrid bi-exponential and gamma variate model fitting of the AIF was performed prior to kinetic model analysis [ 40 , 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…The ETM has been adopted in this study as previous application of this model with low-spatial resolution HT data sets derived from DTR DCE-MRI was found to give both tissue-validated and clinically relevant kinetic parameter estimates. 4,5,30 Recent studies have also shown through a model selection process using the Akaike information criteria, that the ETM was one of the optimal models in pharmacokinetic analysis of DCE-MRI data in brain tumors 42 and papillary thyroid carcinoma. 43 One limitation of the ETM is that the derived parameter K trans is a hybrid parameter reflecting both capillary blood flow and permeability effects, 44,45 and future studies incorporating the high spatiotemporal resolution DCE data provided by the LEGATOS method and other DCE-MRI models, which seek to further separate out such effects should, therefore, be undertaken.…”
Section: T a B L Ementioning
confidence: 99%